The Influence of Ethnic Relations on the Political Orientation of the Simpang Selayang Community in Medan City - Sugiharto Sugiharto; Mulhady Putra; Pinta Yosepin Turnip; Nurida Hana Simamora (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2025)
This study aims to analyze the influence of ethnic relations on the political orientation of the community in Simpang Selayang Village, Medan City. The research method used is descriptive qualitative with data collection techniques through interviews and documentation. The data analysis techniques applied include data reduction, data presentation, and data verification according to Miles and Huberman. This study focuses on two main problem formulations, namely the influence of ethnic relations on political issues and the influence of ethnic relations on political orientation. The results of the study indicate that ethnic identity plays an important role in determining individual political preferences. Ethnic identity serves as a frame of reference that guides political behavior, including in general elections and other political participation. Solidarity between ethnic groups often strengthens political support for candidates who have the same ethnic affiliation, creating a voting pattern that is strongly influenced by ethnic factors. The research findings also reveal that political issues that are relevant to the local community are influenced by the social and cultural context of each tribe. political programs that emphasize local economic development and preservation of tribal culture tend to get greater support. This suggests that understanding the socio-cultural context of ethnic groups is key to formulating effective and inclusive political policies. This study provides new insights into the dynamics of politics in a multi-ethnic society and emphasizes the importance of inclusive policies that take into account ethnic diversity to promote social harmony and political stability in Simpang Selayang Village.